Development of a pocket book on biopesticides extracted from chili peppers (Capsicum annuum L.) for controlling leafworm pests (Plutella xylostella) - Istiqamah Istiqamah; Muhammad Rijal Saputra (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2026)
The use of chemical pesticides has long-term impacts on both the environment and living organisms. One alternative to chemical pesticides is to replace them with biopesticides made from organic materials that are more environmentally friendly. The use of chili pepper (Capsicum annuum L.) waste is a potential solution because it contains capsaicin, which is toxic to leafworm pests (Plutella xylostella). Books on the use of rotten chili pepper waste as biopesticides are very limited and need to be developed so that the benefits of biopesticides can be utilized by the community. Developing this pocketbook also serves as a practical guide for the use of chili pepper biopesticides to control pests, thereby helping farmers reduce their dependence on chemical pesticides. The objective of this study is to describe the validity of the chili pepper (Capsicum annuum L.) biopesticide handbook for controlling leaf caterpillars.  This type of research is development research with a qualitative and quantitative approach. The development method used is Educational Design Research (EDR), which includes the preliminary research stage, the prototyping phase, and the assessment phase, but in this study, it is limited to the prototyping phase. The data obtained is validity data for the handbook, collected through interviews with three validators, including subject matter experts, media experts, and language experts. This validity data was then analyzed descriptively. The validation results by the experts yielded a validity score of 84.6%, indicating that the book is suitable for use. Thus, the development of this pocketbook is expected to serve as a practical solution in supporting sustainable agriculture that is safer for the environment and human health. Abstrak. Penggunaan pestisida kimia memiliki dampak jangka baik terhadap lingkungan maupun terhadap makhluk hidup. Salah satu alternatif pengganti pestisida kimia tersebut adalah dengan menggantinya dengan biopestisida yang terbuat dari bahan organik yang lebih ramah lingkungan. Pemanfaatan limbah cabai rawit (Capsicum annuum L.) menjadi solusi potensial karena mengandung capsaicin yang bersifat toksik bagi hama ulat daun (Plutella xylostella). Buku mengenai pemanfaatan limbah cabai rawit busuk sebagai biopestisida ini sangat terbatas dan perlu dikembangkan agar manfaat biopestisida ini dapat digunakan oleh masyarakat. Mengembangkan buku saku ini juga sebagai panduan praktis pemanfaatan biopestisida cabai rawit untuk mengendalikan hama, sehingga dapat membantu petani mengurangi ketergantungan pada pestisida kimia.  Tujuan penelitian ini adalah untuk mendeskripsikan validitas buku saku biopestisida cabai rawit (Capsicum annuum L.) untuk  pengendalian hama ulat daun. Jenis penelitian ini adalah jenis penelitian pengembangan dengan pendekatan kualitatif dan kuantitatif. Metode pengembangan yang digunakan adalah Educational Design Research (EDR) yang meliputi tahapan pendahuluan (Preliminary Research), tahap pengembangan (Prototyping Phase), dan tahapan penilaian (Assessment Phase), namun dalam penelitian ini dibatasi sampai tahap pengembangan (Prototyping Phase). Data yang didapat merupakan data validitas buku yang diperoleh melalui angket wawancata terhadap tiga (3) orang validator yang meliputi ahli materi, media, dan bahasa. Data validitas tersebut kemudian dianalisis secara deskriptif. Hasil validasi buku saku oleh para ahli menghasilkan skor validitas 84,6%, yang menunjukkan bahwa buku ini layak digunakan. Dengan demikian, pengembangan buku saku ini diharapkan dapat menjadi solusi praktis dalam mendukung pertanian berkelanjutan yang lebih aman bagi lingkungan serta kesehatan manusia.